2015
DOI: 10.1080/15732479.2015.1071855
|View full text |Cite
|
Sign up to set email alerts
|

Response modification factor of elevated water tanks with reinforced concrete pedestal

Abstract: A probabilistic method based on FEMA P695 is employed for validating the response modification factor of reinforced concrete pedestals in elevated water tanks. In the current codes and standards, the response modification factor of elevated water tanks is mainly based on engineering judgement. Ten models of elevated water tanks with different tank sizes and pedestal heights are selected for the investigation. Initially, the prototypes are designed based on the current codes and standards. Next, the finite elem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 10 publications
(10 reference statements)
0
4
0
Order By: Relevance
“…Additionally, much research has been conducted on EWT's seismic performance with reinforced concrete (RC) water tanks and frame staging [8,9]. However, a limited number of studies have investigated the seismic performance of EWT with RC water tanks and RC shafts [10][11][12][13].…”
Section: Introductionmentioning
confidence: 99%
“…Additionally, much research has been conducted on EWT's seismic performance with reinforced concrete (RC) water tanks and frame staging [8,9]. However, a limited number of studies have investigated the seismic performance of EWT with RC water tanks and RC shafts [10][11][12][13].…”
Section: Introductionmentioning
confidence: 99%
“…The seismic response of concrete and steel tanks was extensively investigated through experimental and numerical methods [5][6][7][8]. Factors that affect the seismic response of tanks include the tank size [9], the soil-structure interaction [10], and the fluid-structure interaction [11]. Regarding the optimized design of elevated RC water tanks, to the best of the authors' knowledge, there was no research conducted to date.…”
Section: Introductionmentioning
confidence: 99%
“…The results of the survey indicated the validity and correctness of the R factor used in the current codes and standards. It showed that the size of the tanks affects the nonlinear seismic response behavior of the elevated water tanks (Ghateh et al 2016).…”
Section: Introductionmentioning
confidence: 99%